Observation of replica symmetry breaking in disordered nonlinear wave propagation. Issue 1 (December 2017) - Pierangeli, Davide; Tavani, Andrea; Di Mei, Fabrizio; Agranat, Aharon; Conti, Claudio; DelRe, Eugenio
Abstract A landmark of statistical mechanics, spin-glass theory describes critical phenomena in disordered systems that range from condensed matter to biophysics and social dynamics. The most fascinating concept is the breaking of replica symmetry: identical copies of the randomly interacting system that manifest completely different dynamics. Replica symmetry breaking has been predicted in nonlinear wave propagation, including Bose-Einstein condensates and optics, but it has never been observed. Here, we report the experimental evidence of replica symmetry breaking in optical wave propagation, a phenomenon that emerges from the interplay of disorder and nonlinearity. When mode interaction dominates light dynamics in a disordered optical waveguide, different experimental realizations are found to have an anomalous overlap intensity distribution that signals a transition to an optical glassy phase. The findings demonstrate that nonlinear propagation can manifest features typical of spin-glasses and provide a novel platform for testing so-far unexplored fundamental physical theories for complex systems. Replica symmetry breaking describes identical copies of a randomly interacting system exhibiting different dynamics. Here, Pierangeli et al. observe this critical phenomenon in the optical wave propagation inside a disordered nonlinear waveguide.